Removal of Iron(II) Using Ni/Al Layered Double Hydroxide Intercalated with Keggin Ion - Lesbani, Aldes Lesbani; Normah, Normah; Palapa, Neza Rahayu; Taher, Tarmizi; Andreas, Roy; Mohadi, Risfidian (Molekul, 2020)
Layered double hydroxide (LDH) Ni/Al-NO3 was synthesized using a coprecipitation method under base condition following with intercalation using Keggin ion [a-SiW12O40]4- to form Ni/Al-[a-SiW12O40] LDH. The LDHs were characterized using XRD, FTIR, BET, and pHpzc analyses. Furthermore, LDHs were applied as adsorbent of iron(II) from aqueous solution. The adsorption process was studied through the effect of adsorption time, the concentration of iron(II), and temperature adsorption. The results show the interlayer distance of LDHs was increased from 7.408 Ã… to 10.533 Ã… after intercalation process. The adsorption of iron(II) on LDHs showed that adsorption of iron(II) on both LDHs follows pseudo first-order kinetic model with R2 value is close to one. The adsorption process was spontaneous, with adsorption capacity up to 36.496 mg g-1.